2021
DOI: 10.1089/neu.2020.7061
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Blast Promotes Chronic Aversion to Neutral Cues Encountered in the Peri-Blast Environment

Abstract: Repetitive mild traumatic brain injury (mTBI) has been called the "signature injury" of military Servicemembers in the Iraq and Afghanistan wars and is highly comorbid with posttraumatic stress disorder (PTSD). Correct attribution of adverse blast-induced mTBI and/or PTSD remains challenging. Preclinical research using animal models can provide important insight into the mechanisms by which blast produces injury and dysfunction-but only to the degree by which such models reflect the human experience. Avoidance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 44 publications
6
19
0
Order By: Relevance
“…Previous work in animal models supports the notion of brain injury as a risk factor for adverse health risk behaviors, including substance misuse/abuse (Cernak et al, 2001;Lim et al, 2015;Lowing et al, 2014;Muelbl et al, 2018;Nawarawong et al, 2019;Perez-Garcia et al, 2019;Schindler et al, 2017;Schindler et al, 2020;Vonder Haar et al, 2019). Indeed, using our established mouse model of blast exposure (Huber et al, 2013;Logsdon et al, 2020;Meabon et al, 2016;Schindler et al, 2017;Schindler et al, 2020), we previously demonstrated increased novelty-seeking behavior at acute (7 days) and chronic (1 month) time points following injury (Schindler et al, 2017). Likewise, increased risk-like behavior has also been reported following mild impact TBI (Krukowski et al, 2020;Mouzon et al, 2014).…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…Previous work in animal models supports the notion of brain injury as a risk factor for adverse health risk behaviors, including substance misuse/abuse (Cernak et al, 2001;Lim et al, 2015;Lowing et al, 2014;Muelbl et al, 2018;Nawarawong et al, 2019;Perez-Garcia et al, 2019;Schindler et al, 2017;Schindler et al, 2020;Vonder Haar et al, 2019). Indeed, using our established mouse model of blast exposure (Huber et al, 2013;Logsdon et al, 2020;Meabon et al, 2016;Schindler et al, 2017;Schindler et al, 2020), we previously demonstrated increased novelty-seeking behavior at acute (7 days) and chronic (1 month) time points following injury (Schindler et al, 2017). Likewise, increased risk-like behavior has also been reported following mild impact TBI (Krukowski et al, 2020;Mouzon et al, 2014).…”
Section: Introductionsupporting
confidence: 72%
“…The blast overpressure (BOP) peak intensity (psi), initial pulse duration (ms), and impulse (psi▪ms) used were in keeping with mild blast TBI (19.9 psi +/− 0.14 psi) [32]. Under these experimental conditions, the overall survival rate exceeded 95%, with blast-exposed mice appearing comparable to sham-exposed mice by inspection 2-4 h postblast exposure as previously reported (Huber et al, 2013;Logsdon et al, 2020;Meabon et al, 2016;Schindler et al, 2017;Schindler et al, 2020).…”
Section: Animals and Mouse Model Of Blast Overpressurementioning
confidence: 65%
See 3 more Smart Citations